Political Technologies of Memory: Uses and Appropriations of Artefacts that Register and Denounce State Violence. (23rd January 2019) - Bernasconi, Oriana; Lira, Elizabeth; Ruiz, Marcela
ABSTRACT∞ : This article contributes to understanding the role of technologies during political violence and in transitional justice contexts, studying a case that was contemporaneous with the transnational construction of human rights activism. Examining documentation technologies that sustained nonviolent civic resistance to state terrorism during Chile's Augusto Pinochet dictatorship (1973–1990), the article highlights the role of technology in creating the kind of register that has become commonplace in human rights settings. Considering the use of technology over time, we propose the notion of 'political technologies of memory' to name the lasting effects of artefacts that register and denounce human rights violations. We discuss as 'transposition' the operations by which technologies may be transferred and appropriated, transcending their initial production context and purpose. We offer examples of registry technologies' transposition into transitional justice mechanisms, showing how one such example was represented through an artwork that engaged Chilean society in an ongoing transitional justice conversation.